Emergency management of decompensated peripartum cardiomyopathy - Lata Indu; Gupta Renu; Sahu Sandeep; Singh Harpreet (Journal of Emergencies, Trauma and Shock, 2009)
Peripartum cardiomyopathy (PPCM) is a rare life-threatening cardiomyopathy of unknown cause that occurs in the peripartum period in previously healthy women. [1] the symptomatic patients should receive standard therapy for heart failure, managed by a multidisciplinary team. The diagnosis of PPCM rests on the echocardiographic identification of new left ventricular systolic dysfunction during a limited period surrounding parturition. Diagnostic criteria include an ejection fraction of less than 45%, fractional shortening of less than 30%, or both, and end-diastolic dimension of greater than 2.7 cm/m 2 body surface-area. This entity presents a diagnostic challenge because many women in the last month of a normal pregnancy experience dyspnea, fatigue, and pedal edema, symptoms identical to early congestive heart failure. There are no specific criteria for differentiating subtle symptoms of heart failure from normal late pregnancy. Therefore, it is important that a high index of suspicion be maintained to identify the rare case of PPCM as general examination showing symptoms of heart failure with pulmonary edema. PPCM remains a diagnosis of exclusion. No additional specific criteria have been identified to allow distinction between a peripartum patient with new onset heart failure and left ventricular systolic dysfunction as PPCM and another form of dilated cardiomyopathy. Therefore, all other causes of dilated cardiomyopathy with heart failure must be systematically excluded before accepting the designation of PPCM. Recent observations from Haiti [2] suggest that a latent form of PPCM without clinical symptoms might exist. The investigators identified four clinically normal postpartum women with asymptomatic systolic dysfunction on echocardiography, who subsequently either developed clinically detectable dilated cardiomyopathy or improved and completely recovered heart function.